Hubungan Kebiasaan Konsumsi Ikan dan Asupan Protein Hewani dengan Kejadian Stunting Batita di Pulau Pasaran Kotamadya Bandar Lampung - Anggun Rusyantia (Jurnal Surya Medika (JSM), 2018)
As the age and nutritional intake are lower than the need, and the high burden of infectious diseases in early life, most infants in Indonesia continue to experience a decline in nutritional status with peak decline at approximately 18-24 months of age. The prevalence of stunting in children year 2013 is 37.2%. Lampung Province is included into 15 provinces with a serious category or has a prevalence of ≥40 percent (Riskesdas, 2013). The purpose of this study is to identify the relation between fish consumption habits and animal protein intake with stunting in a toddler. This was a cross-sectional study with 49 toddlers as a sample who live in Pulau Pasaran Bandar Lampung. There was no significant relationship between the frequency of fish consumption (p = 1,000) and there was a significant relationship between the consumption of animal protein with the stunting(p = 0.002). It is necessary to establish a program of growth monitoring of children in the form of regular height measurement at least every 3 months in the second and third year and every 6 months in the fourth and fifth year at posyandu level with the assistance of nutritionist of puskesmas. It is also suggested that diversify the daily menu for toddlers is needed by adding some of the animal protein in snacks and main meals to increase consumption of animal protein.